The effect of pioglitazone on weight, lipid profile and liver enzymes in type 2 diabetic patients. (April 2015) - Aghamohammadzadeh, Nasser; Niafar, Mitra; Dalir Abdolahinia, Elham; Najafipour, Farzad; Mohamadzadeh Gharebaghi, Saeed; Adabi, Khadijeh; Dalir Abdolahinia, Elaheh; Ahadi, Hamidreza
Background: Pioglitazone is one of the antidiabetic agents used in the management of type 2 diabetes mellitus (DM). The effect of pioglitazone on blood glucose, lipid profile, liver enzymes and weight has been shown with conflicting results. In this study we aim to evaluate the effect of pioglitazone on the weight, lipid profile and liver enzymes in patients with DM. Methods: In this single-arm clinical trial, 110 poorly controlled diabetic type 2 patients (63.6% female with mean age of 54.26 ± 8.96 years) who were on maximal dosage of metformin and glibenclamide were enrolled. Patients were treated with pioglitazone for 3 months and laboratory. Fasting blood sugar (FBS), haemoglobin A1C (HbA1C), cholesterol, triglyceride, low-density lipoprotein (LDL) and high-density lipoprotein (HDL), alkaline phosphatase (ALK-P), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and weight changes were measured before and at the end of the study. Results: The levels of FBS ( p < 0.001), HbA1c ( p < 0.001), triglyceride ( p = 0.001), ALT ( p = 0.005) and ALK-P ( p = 0.001) were significantly decreased, but weight was significantly increased ( p < 0.001) after the intervention. There were no significant difference in cholesterol, LDL and HDL values before and after study. Conclusion: Although pioglitazone causes a significant decrease in FBS, HbA1C and triglyceride levels, it is associated with weight gain, which would limit its utility. IRCT registration code: IRCT201209276712N2